Analysis of immersed geological formations for Bekhmeh dam reservoir/ Erbil - Najim Abdula K. Al-Kraaey; Fuad A.M. Al- Omary; Sabbar Abdulla S. Al-Kaisy (Tikrit Journal of Pure Science, 2022)
Geological formations areas measurements for immersion level have been got for the Bekhmeh dam reservoir depending on the digital elevation model (DEM) with resolution (10 m) and Global Mapper-GIS software, which deal with the spatial analysis and get the spatial data of the landforms. The immersed area of each geological formation was determined separately for all levels, from the minimum level (380m) to the maximum one (600m) above the sea level, with (1 m) interval